MENINGKATKAN MOTIVASI DAN PERILAKU BERAGAMA SISWA MI (STUDI LITERASI) - Muhammad Fatkhan Muallifin (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2018)
Lack of religious motivation, makes students less responsible. Students just want to get good grades without having to learn by cheating. It is necessary to increase students' motivation and religious behavior in order to have good morality without having to do behavior that is out of religious values. Not only in terms of learning but also at home and in the madrasa. Therefore, the researchers raised the problem, namely: 1) How MI's efforts to increase religious motivation in students 2) How do MI improve religious behavior in students and 3) What are the supporting and inhibiting factors faced by MI in increasing motivation and behavior religion to students. This study uses literature study research by examining related theories to improve MI students' motivation and religious behavior. The results of various literature reviews will be used to identify increasing religious motivation and behavior of MI students. The results of the analysis show that efforts to improve the religious motivation of MI students can be realized in several methods, namely giving rewards, giving praise, providing added value, sanctions or punishment, creating healthy competition, instilling a sense of responsibility for an obligation and character education. The way to improve religious behavior in the dimensions of religious practice is realized in the main effort, namely first to enter into the intraculikuler, the second in the supporting program. Supporting programs can be classified daily and annually. For daily activities include remembrance after obligatory prayer, prayer, Dhuha prayer, noon prayer and Asr prayer, row class (murajaah), qiraati, and closing aurat. While the annual activities include Islamic boarding schools, qurban, and fasting. There are 2 factors that influence the school's efforts to improve religious behavior, namely supporting factors and inhibiting factors. For the first, supporting factors can be classified into two factors: school factors and collaboration factors with student guardians. For school factors include the participation of school residents, madrasah environment, school facilities and infrastructure. For factors of collaboration with student guardians include student guardian meetings, Ramadhan Monitoring Books and similar objectives for all school and student guardians. The second factor is the inhibiting factor of the school's efforts to improve religious behavior which comes from lack of family attention and negative interactions in the community.